Japan Tobacco International: To 'be the most successful and respected tobacco company in the world'. Issue 3 (4th March 2017) - MacKenzie, Ross; Eckhardt, Jappe; Widyati Prastyani, Ade
ABSTRACT: Japan Tobacco International (JTI) is the international division of Japan Tobacco Incorporated, and the world's third largest transnational tobacco company. Founded in 1999, JTI's rapid growth has been the result of a global business strategy that potentially serves as a model for other Asian tobacco companies. This paper analyses Japan Tobacco Incorporated's global expansion since the 1980s in response to market opening, foreign competition, and declining share of a contracting domestic market. Key features of its global strategy include the on-going central role and investment by the Japanese government, and an expansion agenda based on mergers and acquisitions. The paper also discusses the challenges this global business strategy poses for global tobacco control and public health. This paper is part of the special issue 'The Emergence of Asian Tobacco Companies: Implications for Global Health Governance'.